Ex-PTPN-II Cultivation Rights Issues and The Current Development - Kennedy Nasib P. Sibarani; Jamaluddin Mahasari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: Plantation Limited Company (PTPN)-II has been underway since 2002 and has been 18 years unfinished until now. The problems faced in its settlement are not only issues of land administration but are related to various aspects. This research uses empirical methods with the description approach. The type of data used is primary and secondary data. Data collection is done by interview and a literature study with primary, secondary, and tertiary legal materials. The results of this study are to explain and give an overview of the very long process of land settlement in the ex-PTPN-II cultivation rights in North Sumatra Province. In conclusion, it is necessary to revise Decree of the Head of the National Land Agency Number 42/HGU/BPN/2002 concerning the granting of an extension of the term of the land use rights located in the Deli Serdang Regency, North Sumatra Province, Decree of the Head of the National Land Agency Number 43/HGU/BPN/2002 concerning the granting of an extension of the term of the land use rights located in the Langkat Regency, North Sumatra Province, and Decree of the Head of the National Land Agency Number 44/HGU/BPN/2002 concerning the rejection of the application for the extension of the period of the land use rights located in the city of Binjai, North Sumatra Province, respectively dated November 29, 2002. It needs to be formulated legal consensus to accelerate the completion of ex-PTPN-II cultivation rights, and the President makes a Presidential Decree, which can be the legal basis for its resolution.Intisari: Penyelesaian masalah Hak Guna Usaha (HGU) Ex. PTPN-II telah berlangsung sejak tahun 2002 dan telah 18 tahun belum selesai hingga sekarang. Masalah yang dihadapi bukan hanya masalah administrasi pertanahan tetapi terkait dengan berbagai aspek. Penelitian ini menggunakan metode empiris dengan pendekatan deskriptif. Jenis data yang digunakan adalah data primer dan sekunder. Pengumpulan data dilakukan dengan wawancara dan studi literatur dengan materi hukum primer, sekunder, dan tersier. Hasil penelitian ini adalah menjelaskan dan memberikan gambaran umum dari proses penyelesaian lahan yang sangat lama terhadap HGU ex PTPN-II di Provinsi Sumatera Utara. Kesimpulannya adalah perlu untuk merevisi Keputusan Kepala Badan Pertanahan Nasional Nomor 42 / HGU / BPN / 2002, Keputusan Kepala Badan Pertanahan Nasional Nomor 43 / HGU / BPN / 2002, dan Keputusan Kepala Tanah Nasional Badan Nomor 44 / HGU / BPN / 2002. Perlu dirumuskan secara legal konsensus untuk mempercepat penyelesaian HGU ex-PTPN-II, dan diperlukan Keputusan Presiden, yang dapat menjadi dasar hukum untuk penyelesaiannya